The Influence of Product Quality and Price Perception on The Decision to Purchase Pixy Cosmetic Products in Watson, East Jakarta - Nurmaningsih; Maulidia, Rafiqa; Nissrina , Novia Eka (PT. Maju Malaqbi Makkarana, 2024)
The aim of this research is to determine the influence of product quality and price perception on purchasing decisions for Pixy cometics products at Watson, East Jakarta. The analysis method in this research uses primary data. The test stages carried out were validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis tests, T test, F test, and coefficient of determination test (R2). The data used in this research used a questionnaire questionnaire via Google Form and consisted of 100 respondents. The sampling method in this research is non-probability sampling with a purposive sampling technique. The testing tool used in this research is IBM SPSS 26 software. The results of this research show that simultaneously the product quality variable and the price perception variable have a significant influence on purchasing decisions for Pixy cosmetic products at Watson, East Jakarta. Partially, the product quality variable has a positive and significant effect on purchasing decisions, and the price perception variable has a positive and significant effect on purchasing decisions for consumers of Pixy cosmetic products at Watson, East Jakarta.